ENGLISH DICTION IN FACEBOOK STATUS - Lisdiana, Agnes; Rufinus, Albert; Giovani, Wanda (JOEEL (Journal of English Education and Literature), 2022)
The objective of this study was to determine the kinds of English Dictions commonly occured in the students Facebook status. It was the analysis on the use of English of the students of Pamane Talino college of Education and the reasons behind the writing of the dictions by students STKIP Pamane Talino Landak Regency. The method used was a descriptive qualitative research method. The subjects in this study were English students at STKIP Pamane Talino, Landak Regency, for the 2019&2020 year of study, totaling 30 students. Sources of data were: (1) sources (informants), (2) places and events, (3) documents. Data collection techniques used in this study are (1) documents, (2) interviews. The results of this study are: (1) The types of English diction used by the students are as follows: (a) formal diction, (b) informal diction. The college students tend to use informal diction (93.3%) rather than formal diction (6.7%) in writing status on their Facebook. It is because writing informal diction is easy, simple, and free to express their feeling and thinking. Many of them claimed that have limited vocabulary. This research also showed the background of the students’ reason in writing informal diction on their Facebook status is because they want to share their feeling. (2) The reasons of writing English diction by students are (a) The students need to share their experience and situation in their daily life, (b) The students inspired from words of motivation and lyrics of song, (c) The students want to express the current idea that pop in their mind. This is because most of the students tend to write in English to practice their writing skill and vocabulary.